Incidence of Cronobacter sakazakii in Powdered Infant Formula Milk Available in Malaysia - Norrakiah Abdullah Sani,; Masomeh Ghassem,; Abdul Salam Babji,; Uma Priya Kupusamy,; Norizan Jaafar, (Universiti Kebangsaan Malaysia, 2014)
Enterobacter sakazakii previously known as ‘yellow-pigmented E. cloacae’ has been classified as a new genus ‘Cronobacter’ based on taxonomic analysis and geno-and phenotypic evaluation. This pathogenic organism has been associated with rare form of infant meningitis and necrotizing enterocolitis (NEC) with high mortality rate (40-80%). Some cases have been linked to the consumption of contaminated powdered infant formula milk (PIF). The objective of this study was to determine the presence of Cronobacter spp. in PIF sold in Malaysia. A selective chromogenic agar, Brilliance Enterobacter sakazakii (DFI, Oxoid), was used for detection of Cronobacter strains. Presumptive Cronobacter isolates were identified using biochemical tests (API 20E and MicrogenTM) and molecular assays (SYBR Green Real-time PCR and 16S ribosomal DNA sequencing). All presumptive Cronobacter strains produced typical blue-green colonies and non-Cronobacter strains produced yellow colonies on Brilliance Enterobacter sakazakii agar (DFI formulation). A total of 12 presumptive isolates were selected from DFI agar and identified with biochemical and molecular tests. The results indicated prevalence of 12.5% C. sakazakii contamination from 72 PIF samples. Molecular detection methods such as Real-time PCR and 16S rDNA proved to have higher identification percentage compared to the biochemical tests. In this study, it was observed that molecular assays were suitable means for sensitive identification of Cronobacter strains in PIF samples.